Emergent Mental Health Visits to a Pediatric Hospital: Impact on Firearm Storage Practices. Issue 12 (December 2021) - Uspal, Neil G.; Jensen, Jennifer; Sanchez-Erebia, Luis; Strelitz, Bonnie; Schloredt, Kelly; Gallagher, Chelsie; Bradford, Miranda C.; Bennett, Elizabeth; Paris, Carolyn A.
Abstract : Objective: The aims of this study were to describe firearm storage practices in homes of patients evaluated for mental health (MH) complaints at a tertiary care children's hospital and to describe storage practice changes after treatment. Methods: We surveyed families of children with MH complaints presenting to the emergency department or psychiatry unit who stored firearms in their homes between February 12, 2016, and January 14, 2017. Patients and families received standard care, including routine counseling on limiting access to methods of suicide. Participants completed surveys at baseline, 7, and 30 days after discharge. The primary outcome was triple safe firearm storage—storage of firearms unloaded, locked, and with ammunition stored and locked separately. Results: Ninety-one household members of MH patients who stated they had firearms were enrolled at baseline. Seventy-seven (85%) completed at least 1 follow-up survey, and 63 (69%) completed both. At baseline, 21% (19/91) of participants reported engaging in triple safe firearm storage, 26% had an unlocked firearm, 23% had a loaded firearm, and 65% stored ammunition either unlocked or with their firearm. Triple safe storage rates increased to 31% at both 7 days and 30 days. Ten (17%) of 59 ( P < 0.01) participants who did not report triple safe storage at baseline and completed a follow-up survey changed to reporting triple safe storage on follow-up. Conclusions: The majority of firearm-storing family members of children with MH complaints do not follow triple safe storage practices. Storage practices modestly improved after an emergent MH visit, but over two thirds of participants reported unsecured or partially secured firearms 7 and 30 days later. Abstract : Supplemental digital content is available in the text.